Measurement of ηc production in untagged two-photon collisions at LEP - Dova, María Teresa (1993)
A study of twelve distinct decay channels of the ηc has been performed with the L3 detector at LEP, for an integrated luminosity of 30 pb−1. Summing all channels, 28 candidate events have been identified, with an estimated background of 11 events. The two-photon radiative width is evaluated to be Γγγ(ηc ) = 8.0 ± 2.3 ± 2.4 keV.